GABAA increases calcium in subventricular zone astrocyte-like cells through L- and T-type voltage-gated calcium channels - Young, Stephanie Z.; Platel, Jean-Claude; Nielsen, Jakob V.; Jensen, Niels A.; Bordey, Angelique (Frontiers in Cellular Neuroscience, 2010)
In the adult neurogenic subventricular zone (SVZ), the behavior of astrocyte-like cells and some of their functions depend on changes in intracellular Ca2+ levels and tonic GABAA receptor activation. However, it is unknown whether, and if so how, GABAA receptor activity regulates intracellular Ca2+ dynamics in SVZ astrocytes. To monitor Ca2+ activity selectively in astrocyte-like cells, we used two lines of transgenic mice expressing either GFP fused to a Gq-coupled receptor or DsRed under the human glial fibrillary acidic protein (hGFAP) promoter. GABAA receptor activation induced Ca2+ increases in 40-50% of SVZ astrocytes. GABAA-induced Ca2+ increases were prevented with nifedipine and mibefradil, blockers of L- and T-type voltage-gated calcium channels (VGCC). The L-type Ca2+ channel activator BayK 8644 increased the percentage of GABAA-responding astrocyte-like cells to 75%, suggesting that the majority of SVZ astrocytes express functional VGCCs. SVZ astrocytes also displayed spontaneous Ca2+ activity, the frequency of which was regulated by tonic GABAA receptor activation. These data support a role for ambient GABA in tonically regulating intracellular Ca2+ dynamics through GABAA receptors and VGCC in a subpopulation of astrocyte-like cells in the postnatal SVZ.